PATOGE geometry transformation board: A teaching aid to enhance junior high school students' conceptual understanding - Waluyo, Mohamad; Nawfa, Zulfatun (Indonesian Journal of Science and Mathematics Education, 2024)
Geometric transformation is a vital mathematics topic that should be learned at the junior high school level. Students often consider This material difficult because it is abstract and lacks concreteness. One effort to overcome this difficulty is by using teaching aids. This study aims to develop a geometric transformation board teaching aid to improve the conceptual understanding of 9th-grade junior high school students. This research employs a research and development method. The research sample consists of 17 9th-grade junior high school students. The results show that using the geometric transformation board teaching aid can enhance the conceptual understanding of 9th-grade students. The average student learning outcomes evidence this increase from 57.65 to 79.41. This study implies that PATOGE can effectively make abstract mathematical concepts more concrete and easier to understand.